ENHANCEMENT OF DISSOLUTION OF CANDESARTAN CILEXETIL - C, APARNA; M, ANUSHA; B, MANISHA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The main aim of our investigation was to enhance the dissolution of Candesartan Cilexetil (CC), a prodrug of Candesartan, used in the treatment of hypertension. CC bioavailability is dissolution rate limited. The drug was formulated using various excipients such as surfactants, and liquid lipids to improve solubility, dissolution, and hence bioavailability. Methods: The solubility of CC was determined at 25°C by shake flask method and those showing maximum solubility were selected for the formulation of CC. In vitro dissolution studies were done in different media in pH 6.8 phosphate buffer with 1% SLS, tween 20, and 0.1 N HCl with 1% SLS. The surface morphology of LBDDS was studied with scanning electron microscope (SEM) and the crystallinity of the drug and the formulation were studied using X-ray diffraction (XRD). Results: CC showed maximum solubility in transcutol and labrasol, which, hence, were selected as excipients for the formulation of CC capsules. Drug release was high in 0.1 N HCl with 1% SLS and, hence, was selected as the dissolution medium. The dissolution profile for formulation F5 containing the drug with transcutol and labrasol showed the highest drug release among all formulations, that is, 94.09%. The SEM of the F5 formulation showed that the drug was completely embedded into the lipid matrix and particles were spherical and porous with a size of around 25 μ. XRD of formulation F5 indicated the absence of crystallinity in CC capsules containing transcutol and labrasol. Conclusion: It was concluded that CC containing transcutol and labrasol significantly increases the solubility and dissolution of the drug.